2020
DOI: 10.1016/j.ijantimicag.2020.106002
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting aminocoumarins for the treatment of melioidosis

Abstract: Highlights Aminocoumarins can be used to treat acute pulmonary melioidosis in a murine model. Formulation with l -tyrosine or dl -tryptophan enhances the bioactivity of aminocoumarins. Utility of Galleria mellonella larvae for in vivo drug efficacy screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These in vivo studies were initiated as an extension of our earlier in vitro studies with five bacterial biothreat agents [ 8 ]. The animal investigations with B. pseudomallei also expanded upon those described by Willcocks et al [ 9 ]. In the latter, Novo and other aminocoumerins were evaluated for in vivo potency against B. pseudomallei .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These in vivo studies were initiated as an extension of our earlier in vitro studies with five bacterial biothreat agents [ 8 ]. The animal investigations with B. pseudomallei also expanded upon those described by Willcocks et al [ 9 ]. In the latter, Novo and other aminocoumerins were evaluated for in vivo potency against B. pseudomallei .…”
Section: Discussionmentioning
confidence: 82%
“…The objective of our research was to repurpose and evaluate the antimicrobial agent novobiocin (Novo), an aminocoumarin class antibiotic, as a novel therapeutic approach to counteract natural or engineered resistance to conventional antibiotics, promote more complete and rapid clearance of infection, and increase survival of mice exposed to a lethal infection with the bacterial threat agents of melioidosis and anthrax. Novo is a potent bactericidal antibiotic having broad in vitro efficacy against several high consequence pathogens [ 7 , 8 , 9 ]. It is a licensed but under-utilized early-generation antibiotic which exhibits low effective concentrations against highly disparate agents such as Francisella tularensis , the pathogenic Burkholderia spp., and Bacillus anthracis [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coumermycin was also shown to be effective against Burkholderia species and to have superior properties than novobiocin. Willcocks et al ( 49 ) found that coumermycin has increased activity against B. pseudomallei in G. mellonella larvae compared to novobiocin and protected against acute melioidosis in a murine infection model ( 49 ). They attributed increased protection to a longer half-life in plasma compared to novobiocin.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia pseudomallei (BP) is a gram-negative, environmental saprophyte predominately found in the soil and surface groundwater of endemic tropical and subtropical regions worldwide [ 1 , 2 ]. BP is the etiological agent of melioidosis, a life-threatening disease that accounts for approximately 89,000 deaths per year worldwide [ 2 - 6 ]. Diabetes mellitus remains a major risk factor for melioidosis; therefore, the rising global diabetes pandemic could further escalate the number of deaths attributed to melioidosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%